An appraisal of the Guttinger statistic 611 - (:unkn) unknown (College of Aeronautics, 1966)
Using the Systems Design procedure developed at Cranfield, an appraisal of the Guttinger Statistic 611 has been carried out; in particular, the interface of the machine has been redesigned.